PEMBERIAN PELLET ECENG GONDOK (Echhornia crassipes) TERHADAP PERTUMBUHAN IKAN NILA MERAH (Oreochoromis sp) DI JARING TANCAP - Lumenta, Cyska (Universitas Sam Ratulangi, 2006)
The research of on the growth of red nila fish measuring 10-12 cm in length and 27-32 g in weight feed with pellet containy different compocition of eceng gondok leaf powder has been carried out in Tondano lake, Eris village, Eris district, Minahasa Agency. The arm of this rescearch is to find out with compotition (10%, 20%, 30%) of pellet from eceng gondok lef that have different composition (10%, 20%, 30%) in pellet give the best relative growth, effisiency value and nutrient convertion value in comparison with commercial pellets. The result showed that pellet contaning 10% eceng gondok powder hed the nigest relative growth (195.4%, efficiency value (61.65) and nutrient convertion value (1.6).Â Commercial pellet used as control hower is still relatively better compare with all experimental pellets containing defferent competition of eceng gondok in terms of relative growth, effisiency value and nutrient convertion value.Â Keywords: Red nila (Oreochormis sp), Eceng gondok pellets (Echhornia crassipes), Set net (jaring tancap)